1) (x-2)(x-3)+(x+6)(x-5)-2 (x квадрате-7x+13) при x=5,62) (3m-1)(m+1)+(2m-1)(m-1)-(5m+5)(m-2) при m=0.375

1) (x-2)(x-3)+(x+6)(x-5)-2 (x квадрате-7x+13) при x=5,6 2) (3m-1)(m+1)+(2m-1)(m-1)-(5m+5)(m-2) при m=0.375
Гость
Ответ(ы) на вопрос:
Гость
1)упростим выражение [latex](x-2)(x-3)+(x+6)(x-5)-2 (x^2-7x+13)=(x^2-3x-2x+6) \\ +(x^2-5x+6x-30)-2x^2+14x-26= \\ =x^2-5x+6+x^2-x-30-2x^2+14x-26=8x-50[/latex] подставим вместо х 5,6 [latex]8*5.6-50=-5.2[/latex] 2)упростим выражение: [latex](3m-1)(m+1)+(2m-1)(m-1)-(5m+5)(m-2)= \\ =(3m^2+3m-m-1)+(2m^2-2m-m+1)- \\ (5m^2-10m+5m-10)=(3m^2+2m-1)+ \\ (2m^2-3m+1)-(5m^2-5m-10)= \\ =3m^2+2m-1+2m^2-3m+1-5m^2+5m+10=4m+10[/latex] подставим х=0.375 [latex]4*0.375+10=11.5[/latex]
Не нашли ответ?
Ответить на вопрос
Похожие вопросы